63.1k views
4 votes
FACTORISE;
3D²-2D -8
BY SPLITING THE
MIDDLE TERM​

1 Answer

3 votes

Answer:

(3D +4)(D -2)

Explanation:

The middle term needs to be split into two terms that sum to -2D and have a product of (3d²)(-8) = -24D². You know that -24 has the possible factorizations ...

-24 = -24·1 = -12·2 = -8·3 = -6·4

This last pair of factors has a sum of -2. So, the middle term of the original expression can be split into the two terms -6D and +4D.

3D² -2D -8 = 3D² -6D +4D -8

= 3D(D -2) +4(D -2)

= (3D +4)(D -2)

User Cerissa
by
6.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.